Pengaruh Beban Kerja, Stres Kerja, dan Lingkungan Kerja terhadap Turnover Intention: Studi Kasus PT Gunanusa Utama Fabricators - Dahlia Apriliawati; Fazhar Sumantri; Theysa Sahlani Pratiwi (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
The high level of turnover intention is a serious challenge for organizations in maintaining quality human resources. This phenomenon not only impacts organizational stability, but also reduces overall employee performance and productivity. This research uses a quantitative approach, which is a scientific approach that systematically examines phenomena in a sample and population by using numerically measured data and analyzed using statistical procedures. The population in this study were all employees of PT Gunanusa Utama Fabricators. The sampling technique was carried out using Non-probability sampling method, specifically purposive sampling with a total sample of 50 respondents. The results of the hypothesis show that Workload, Stress and Work Environment together have a significant and positive influence on Turnover Intention. In other words, if these three factors decrease, the tendency of employees to leave the company will also decrease. Conversely, an increase in workload, stress levels and unsupportive work environment conditions will encourage increased employee intention to leave the company. The results of this study indicate that the three aspects simultaneously contribute significantly in influencing employee decisions regarding turnover intention, so that the management of the three is an important key in an effort to reduce the level of employee turnover at PT Gunanusa Utama Fabricators.